Health Care and Government Policy - Abreu, Laurinda (2020)
Government policy refers primarily to the actions planned and implemented by the executive branch of a state to meet its society’s needs. One of the most demanding areas both for policy makers and in terms of people’s expectations is health, which social analysts and historians place among the most dynamic sectors over the last century. This is the focus of this book. It includes examinations of two of the most pressing issues facing national healthcare services today – ‘Health systems at the stage of complexity: the need for collaborative intelligence’ by Constantino Sakellarides et al. and ‘Longer and better lives: the European fountain of youth’ by Patrice Bourdelais – alongside historical analyses covering both earlier periods – ‘Not just one countryside: life chances in preindustrial Sweden’ by Jan Sundin and ‘Health care and poor relief in Portugal: an historical perspective’ by Laurinda Abreu – and more recent times – ‘The roots of the health reform in Spain’ by Enrique Perdiguero-Gil and Josep M. Comelles